Analisis Pertumbuhan Ekonomi Provinsi Jambi 2012-2019 - M Yunus; Novi Mubyarto; Robi Agustin (ILTIZAM Journal of Shariah Economics Research, 2020)
The development achievement of an economic activity can be measured by economic growth. Economic growth will improve if there are activities carried out by humans for the prosperity of the earth and their prosperity. An important factor for increasing economic growth is international trade, one of which is exports. Allah SWT has created in every region and country the advantages and disadvantages. The main factor that also has an influence on the economic development of a country / region is investment activities. Regarding investment in the Al Qur’an, it is clearly stated that investing is a way that is ordered by Allah SWT not to leave the weak generation. In this study, an analysis of the economic growth of the province of Jambi was conducted in 2012-2019. The method used is multiple linear regression analysis. Based on the results of using the R application, there is a significant influence between the export variable and the investment variable on the economic growth variable. The modeling results obtained are Y = 5848.0543 + 0.8886X1 + 0.7929X2. Every increase in exports of 1 billion and investment is considered constant, it will increase economic growth by 0.8886 billion. Every increase in investment of 1 billion and exports are considered constant, it will increase economic growth by 0.7929 billion. The coefficient of determination of 94.06 percent means that the diversity of economic growth variables can be explained by the export and the investment, the remaining 5.94% is explained by other variables not included in the regression model.